Cardiac proteasome functional insufficiency plays a pathogenic role in diabetic cardiomyopathy. (January 2017) - Li, Jie; Ma, Wenxia; Yue, Guihua; Tang, Yaoliang; Kim, Il-man; Weintraub, Neal L.; Wang, Xuejun; Su, Huabo
Abstract: Background: Diabetic cardiomyopathy is a major risk factor in diabetic patients but its pathogenesis remains poorly understood. The ubiquitin-proteasome system (UPS) facilitates protein quality control by degrading unnecessary and damaged proteins in eukaryotic cells, and dysfunction of UPS is implicated in various cardiac diseases. However, the overall functional status of the UPS and its pathophysiological role in diabetic cardiomyopathy have not been determined. Methods and results: Type I diabetes was induced in wild-type and transgenic mice expressing a UPS functional reporter (GFPdgn) by injections of streptozotocin (STZ). STZ-induced diabetes progressively impaired cardiac UPS function as evidenced by the accumulation of GFPdgn proteins beginning two weeks after diabetes induction, and by a buildup of total and lysine (K) 48-linked polyubiquitinated proteins in the heart. To examine the functional role of the UPS in diabetic cardiomyopathy, cardiac overexpression of PA28α (PA28αOE) was used to enhance proteasome function in diabetic mouse hearts. PA28αOE diabetic mice displayed exhibited restoration of cardiac UPS function, as demonstrated by the diminished accumulation of GFPdgn and polyubiquitinated proteins. Moreover, PA28αOE diabetic mice exhibited reduced myocardial collagen deposition, decreased cardiomyocyte apoptosis, and improved cardiac systolic and diastolic function. Conclusion: Impairment of cardiac UPS function is an early event in STZ-induced diabetes. Overexpression of PA28α attenuates diabetes-induced proteotoxic stress and cardiomyopathy, suggesting a potential therapeutic role for enhancement of cardiac proteasome function in this disorder. Highlights: Cardiac UPS function is impaired prior to the onset of diabetic cardiomyopathy. Diabetes diminishes cardiac proteasome function. PA28a overexpression restores cardiac UPS function after diabetes. Enhancement of cardiac proteasome function ameliorates diabetic cardiomyopathy.